JELLY HYPERTENSION MEDICINE FOR THE ELDERLY: FRESH AS A PRACTICAL PREVENTION MEASURE: JELLY OBAT HIPERTENSI UNTUK LANSIA SEGARAN SEBAGAI UPAYA PENCEGAHAN PRAKTIS - Prasetyani Putri, Mardiana; Arshy Prodyanatasari; Mely Purnadianti (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
This community service activity aims to empower the elderly in Segaran Village, Wates District, KediriRegency, through the innovation of making ready-to-consume medicinal jelly as a practical effort to prevent hypertension. Hypertension is a common chronic health problem in the elderly population and can increase the risk of morbidity and mortality. Prevention interventions that are easy to implement and well-received by older people are urgently needed. The implementation method of this activity includes socialisation about hypertension and the importance of prevention, training in making medicinal jelly using natural ingredients with antihypertensive potential, and assistance with packaging and storing products. This activity involves the active participation of older people at every stage. The expected results of this activity are increased knowledge of the elderly about preventing hypertension, skills in making medicinal jelly independently, and the availability of practical natural supplement alternatives that have the potential to support blood pressure control. The medicinal jelly product produced is expected to be a sustainable preventive solution that contributes to improving the quality of life for older people in Segaran Village. Evaluation of the activity will be carried out through observation, interviews, and measuring the level of participant satisfaction.